The Role of Social Media Influencers, Friends, Peers on Travel Decisions for Travelers in Relation to the Highest Impact Among Them That Affect Purchase Intention - Chakraborty, Partha Pratim (Digital Repository of Theses, 2024)
The role of social media and the associated posts done by influencers, friends as well as peers of a traveller is immense in today’s world of travel, and it goes without saying how much it impacts a travel choice. And there is a research gap in understanding in India’s perspective who has more influence among these three - influencers, friends and peers – in family as well as solo travellers’ choice of travel. Hence this study 1) Measures impact of three stake holders on travellers 2) Offers a guide for social media marketing /digital marketing professionals of hospitality brands / tourism boards to understand who to target and with what set of elements/communications & social media channels /applications to get a better understanding of their target customers . This will help many B2C agencies in India to engage better on social media for their clients.